Distinct substrate specificities of the three catalytic subunits of the Trichomonas vaginalis proteasome - Fajtova, Pavla; Hurysz, Brianna M; Miyamoto, Yukiko; Serafim, Mateus Sá M; Jiang, Zhenze; Vazquez, Julia M; Trujillo, Diego F; Liu, Lawrence J; Somani, Urvashi; Almaliti, Jehad; Myers, Samuel A; Caffrey, Conor R; et al. (Protein science, 2024)
The protozoan parasite Trichomonas vaginalis (Tv) causes trichomoniasis, the most common non-viral sexually transmitted infection in the world. Although Tv has been linked to significant health complications, only two closely related 5-nitroimidazole drugs are approved for its treatment. The emergence of resistance to these drugs and lack of alternative treatment options poses an increasing threat to public health, making development of novel anti-Trichomonas compounds an urgent need. The proteasome, a critical enzyme complex found in all eukaryotes has three catalytic subunits, β1, β2, and β5 and has been validated as a drug target to treat trichomoniasis. With the goal of developing tools to study the Tv proteasome, we isolated the enzyme complex and identified inhibitors that preferentially inactivate either one or two of the three catalytic subunits. Using a mass spectrometry-based peptide digestion assay, these inhibitors were used to define the substrate preferences of the β1, β2 and β5 subunits. Subsequently, three model fluorogenic substrates were designed, each specific for one of the catalytic subunits. This novel substrate profiling methodology will allow for individual subunit characterization of other proteasomes of interest. Using the new substrates, we screened a library of 284 peptide epoxyketone inhibitors against Tv and determined the subunits targeted by the most active compounds. The data show that inhibition of the Tv β5 subunit alone is toxic to the parasite. Taken together, the optimized proteasome subunit substrates will be instrumental for understanding the molecular determinants of proteasome specificity and for accelerating drug development against trichomoniasis.
Keywords: inhibitory proteasomu; protozoální proteiny; substrátová specifita; proteasomový endopeptidasový komplex; Catalytic Domain; Proteasome Endopeptidase Complex; Trichomonas vaginalis; Substrate Specificity; katalytická doména; Protozoan Proteins; Proteasome Inhibitors